2015
DOI: 10.1097/btf.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Arthroscopy for Ankle Fracture Care

Abstract: Ankle arthroscopy has been used successfully in the treatment of osteochondral lesions of the talus since the 1980s. Published studies during the 1990s up until present day have shown it as an asset to confirm reduction, limit the surgical exposure and soft-tissue trauma, and to diagnose and treat associated intra-articular pathology in displaced ankle fractures. The objective of this paper is to review the available literature and describe the technique when utilizing arthroscopy in ankle fractures. Level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“… 1 Others have suggested that ankle arthroscopy can provide additional information to help guide diagnosis and treatment. 12 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Others have suggested that ankle arthroscopy can provide additional information to help guide diagnosis and treatment. 12 …”
mentioning
confidence: 99%
“…1 Others have suggested that ankle arthroscopy can provide additional information to help guide diagnosis and treatment. 12 The purpose of this study is to assess the prevalence of intra-articular pathology identified through arthroscopy in patients undergoing operative fixation for ankle fractures. Our hypothesis is that there would be a high incidence of ligamentous and intra-articular pathology definable by arthroscopy that would be neglected if a surgeon was to only perform open reduction and internal fixation (ORIF) of the ankle fracture.…”
mentioning
confidence: 99%